Cashew Nut Quality as Influenced by Microwave Heating Used for Stored Grain Insect Control - Ipsita Das; Narendra G. Shah; Girish Kumar (International Journal of Food Science)
The objective of this work is to investigate the effect of microwave power levels (240, 360, and 480 W) and exposure time (30, 60, 90, 120, 180, and 240 s) on various properties of cashew nuts being used for disinfestation. The nuts were analyzed for moisture content, temperature rise, colour, free fatty acid (FFA) and peroxide value (PV). Experiments were conducted according to the response surface methodology. Increase in microwave power level and exposure time caused a decrease in moisture content, increase in temperature, and change in colour. Microwave treatment to target temperatures of 50–55°C (unfavorable for insect survival) made the PV of cashew nut decrease to 1.10 to 1.66 meq O2/Kg (from an initial value of 2.08 ± 0.05) and FFA value to 0.11 to 0.51% (from an initial value of 0.68 ± 0.03). Though PV and FFA values of microwave treated cashew nut were found to increase after 6 months of storage at room conditions, the values were within the limits for acceptable quality. Microwave treated cashew nuts were free from infestation and rancidity even after 6 months of storage while the untreated nuts were found to be heavily infested at the end of 1 month of storage.